(untitled) (Archaeologia Adriatica, 2022)
The paper discusses a new find of two ceramic fragments from the Neolithic site of Barice in Smilčić recovered in the 2016/17 excavations. The sherds belong to a pottery object that in its morphological characteristics exhibits distinct similarity to roofs of the ceramic house models recorded at a number of sites in the region of southeastern Europe. As all previously recovered finds were interpreted as a special kind of an altar, the find from Smilčić might also belong to the same group of finds, all the more since a similar find was found in an unknown context in the excavations in 1956/59 and 1962. The find was dated to the Middle Neolithic and attributed to the Danilo culture on the basis of motifs executed on the preserved parts of the walls.